PENGARUH LEVERAGE, SUBSIDIARIES DAN AUDIT COMPLEXITYTERHADAP AUDIT DELAY (Studi Empiris pada Perusahaan Manufaktur di Bursa Efek Indonesia) - Bustamam Bustamam; Maulana Kamal (Jurnal Telaah dan Riset Akuntansi, 2010)
Audit delay is an audit solving duration which measured from the date of book year closing to the date of audit report issued. A high quality of financial statement audit could decrease investor and creditor risk in making an investment decision. The advantages of financial statement would decrease if the report isn’t available on time.This research examines the factors influence audit delay. They are leverage, subsidiaries and audit complexity. This research samples take all manufacturing companies are listed in Indonesia Stock Exchange, amount 32 companies that chose based on purposive sampling method by 160 observations. They have undertaken for 5 years from 2004 – 2008.Firstly, data is examined by classical normal linear regresion model (CNLRM) which consist normality, multicollinearity and heteroscedasticity tests. Secondly, it is examined by multiple linear regression using hypothesis to know about the factors have an influencing to audit delay.The result of this research shows that simultaneously, it proves that leverage, subsidiaries and audit complexity have a significant influencing to audit delay at manufacturing companies listed in Indonesia Stock Exchange. Partially, just leverage has a significant influencing to audit delay. Whereas subsidiaries and audit complexity don’t have a significant influencing to audit delay at manufacturing companies listed in Indonesia Stock Exchange. Keywords: Audit Delay, Leverage, Subsidiaries and Audit Complexity.